EXPLORATION OF MATHEMATICAL ABSTRACT LEARNING USING TACTILE AND VISUAL 3D MEDIA: STUDENT MATHEMATICAL ABSTRACTION SKILL - Lapele, Dina Amalya; Papalia, Puput (Universitas Labuhanbatu, 2025)
Purpose-This study aims to explore abstract mathematics learning activities using tactile media and 3D visual media, identify the effect of this learning on students' mathematical abstraction skills, and determine the category of students' mathematical abstraction skills.Methodology-The research approach is a mixed method research. The data collection techniques used were observation and test. The instruments used were observation guidelines and test questions. The qualitative data analysis techniques used were data reduction, data presentation, and drawing conclusions.The quantitative data analysis techniques were descriptive tests and paired sample T test.Findings-Mathematical abstract learning activities using tactile media and 3D visual media are: (1) reflection of initial understanding of abstract concepts; (2) orientation towards the use of abstract concepts in everyday life; (3) measuring the surface area and volume of objects using tactile media; (4) connecting measurement results with mathematical formulas; (5) interpretation of abstract concepts using 3D visual media; (6) stating learning experiences or new things obtained; and (7) drawing conclusions about abstract concepts. There is a strong effect of abstract mathematics learning using tactile media and 3D visual media on students' mathematical abstraction ability. Abstract mathematics learning using tactile media and 3D visual media contributes 25.6% to mathematical abstraction ability, while 74.4% is influenced by other factors. There are 11.54% of students who have high mathematical abstraction ability, 76.92% of students have moderate mathematical abstraction ability, and 11.54% of students have low mathematical abstraction ability.Significance-This findings can be used as a reference for teachers in teaching abstract mathematical concepts. Teachers should have to provide more tactile media in learning activities to give the real experience for students.